The - Trease, Geoffrey (Oxford University Press, 2000)
It's a wonderful time for a boy, of course, but not so much fun for a girl. Athenian woman must stay at home, must not talk to men, must not have intelligent conversations about politics or plays. So when Alexis makes friends with Corinna, agirl ang a foreigner, they have to meet in a secret cave in the hills. There, Alexis writes a p;ay, a comedy called the gadfly, and he and Corinna plan how to enter it for the nest year's Theatre festival